2010
DOI: 10.5009/gnl.2010.4.3.295
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Bacteria in the Pathogenesis of Inflammatory Bowel Disease

Abstract: Crohn's disease (CD) and ulcerative colitis (UC) have features that suggest bacterial involvement, and all genetic models of inflammatory bowel disease (IBD) require the presence of commensal bacteria. CD is associated with innate immune response genes such as NOD2/CARD15 and the autophagy genes ATG16L1 and IRGM. However, IBD responds to immunosuppression, suggesting that any bacteria involved are not acting as conventional pathogens. Molecular techniques are rapidly advancing our knowledge of the gut microbio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 129 publications
0
69
0
Order By: Relevance
“…Studies have demonstrated that not only is MAP a possible source for the ASCA mannan epitope, but also that MAP release a mannosecontaining glycoconjugate that impairs the in vitro ability of monocyte-derived macrophages to kill phagocytosed E. coli. Therefore, as Friswell suggests, MAP might be acting via an indirect pathogenic effect, which would explain its role in pathogenesis and yet not be greatly exacerbated by anti-TNF treatment [44,53] . ASCA may develop a long time before the diagnosis of CD is established.…”
Section: Mycobacterium Avium Paratuberculosismentioning
confidence: 99%
See 3 more Smart Citations
“…Studies have demonstrated that not only is MAP a possible source for the ASCA mannan epitope, but also that MAP release a mannosecontaining glycoconjugate that impairs the in vitro ability of monocyte-derived macrophages to kill phagocytosed E. coli. Therefore, as Friswell suggests, MAP might be acting via an indirect pathogenic effect, which would explain its role in pathogenesis and yet not be greatly exacerbated by anti-TNF treatment [44,53] . ASCA may develop a long time before the diagnosis of CD is established.…”
Section: Mycobacterium Avium Paratuberculosismentioning
confidence: 99%
“…This raises the possibility that a combination of bacterial components, including FimH, linked to GP2, may be presented as a foreign antigen and thus lead to development of anti-GP2 antibodies, in a way analogous to the development of anti-tissue transglutaminase antibodies in celiac disease. As Friswell et al [44] highlight in their review of the role of bacteria in the pathogenesis of IBD, blockade of bacterial entry via M cells represents an important target for therapies. In a very recent paper [45] , certain isolates of E. coli have been shown to be related both with colorectal cancer and IBD.…”
Section: Adherent-invasive E Colimentioning
confidence: 99%
See 2 more Smart Citations
“…The main theories that try to explain Ulcerative Colitis aetiopathogenesis by means of an infectious agent can be summarized as follows: -Dysbiosis hypothesis which implies that an imbalance between beneficial versus detrimental resident intestinal bacterial species may incite chronic inflammatory responses (Friswell et al 2010). -Persistent infection hypothesis which proposes that Ulcerative Colitis may arise as a result of persistent infection with enteric pathogens (Khan et al, 2011).…”
Section: Wwwintechopencommentioning
confidence: 99%